Local development needs and aspirations and the international Square Kilometre Array radio telescope: views from Amandelboom, Williston in South Africa. - Basheer, Arries (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.